Municipalities and educational modernisation: a historical and geographical atlas of municipalities and education in Portugal - Magalhães, Justino (2017)
This text focuses on municipalities from an educational and cultural perspective. Over the last 200 years, municipalities have played a fundamental role in the creation of guiding principles and educational norms and conventions. They have participated in the supply and universalisation of schooling and have contributed to integrating the public sphere and the modern, contemporary political structure. Municipalities as territories, populations, economies, and collective governments backed by written administration have influenced and become the model of the liberal and republican political and educational transformations. They have been crucial to the political, administrative, and socio-cultural constitution of the contemporary state. The school institution has integrated social and political development while educational modernity has brought school cartography closer to demographic, administrative, and cultural cartography. The municipal initiative has played a key role in terms of territorial suitability, modernisation of the school network, and curricular diversity. This text picks up on the main conclusions of the Educational and Cultural Atlas of the Municipalities in Portugal, and places the Portuguese context within a European and western framework. Municipalities are presented as an educational space, with historical and pedagogical importance in the modernisation of schooling, despite a historiographical tendency to dilute them into the state, connecting them to an official perspective of education. The article contains a summary of the Educational Atlas of the Municipalities in Portugal.